Pengujian Praktik Manajemen Laba Dengan Kualitas Audit Sebagai Variabel Pemoderasi - Nico Alexander (Akademi Akuntansi YKPN Yogyakarta, 2023)
This study aims to obtain empirical evidence of the effect of the independence of commissioners and audit committees on earnings management and to test audit quality as a moderating variable can strengthen the relationship between the independence of commissioners and audit committees on earnings management or weaken the relationship between the independence of commissioners and audit committees on earnings management. Audit quality as a moderating variable, because high quality auditors strengthen supervision of management so that the profits reported in the financial statements are more transparant and free from misstatements. Manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2020 were used as samples and 94 companies were selected using purposive sampling method. This study uses path analysis to test the hypothesis. The results showed that the independence of commissioners and audit committees can reduce earnings management behavior by management. Supervisory activities by independent commissioners and audit committees are more effective in reducing opportunistic behavior by management, so that information can be more transparent and have higher quality. This study also provides results that higher audit quality can strengthen the relationship between audit committee independence and earnings management. This study provides information to investors and companies that to prevent earnings management, they can add commissioners and audit committee members from outside the company and also use qualified auditors in providing opinions.